Improving the Teaching of Folk Craft Theory in Technology Classes (Zien Journal of Social Sciences and Humanities, 2022)
The article discusses the study of folk crafts today in the process of training teachers of technology education in higher education institutions in the process of teaching the subject "Folk Crafts and Art Design" and in general secondary schools in the subject "Technology Education", recommendations for improving the theory of folk crafts in technology classes. The importance of development as a social protection, its main directions, the benefits provided by the state to artisans were discussed. The advantages of using the STEAM method in teaching are also shown